3D- Printed Metal Oxides for Biomedical Applications - Mishra D.K.; Kandi R.; Pathak D.K.; Sharma P. (My University, 2025)
The utility of functional bio-composites combining the usefulness of biopolymers and unique characteristics of metal oxides offer a broad range of scope in biomedical applications such as drug delivery, biosensing, bioimaging, cancer therapy, and wound healing. However, the fabrication of complex-shaped bio-constructs and patient-specific scaffolds for regenerative applications of these bio-composites is always challenging and requires accurate fabrication methods. In this context, 3D printing in combination with the principles of engineering, life science, and material science has evolved as one of the emerging techniques for the fabrication of complex-shaped bio-constructs, artificial organs for transplantation, and patient-specific scaffolds for regenerative applications. The combination of metal oxides with the biocompatible polymer matrix helps develop the applications by facilitating their bioavailability. In this chapter, we discuss the major Biofabrication methods of 3D printing to fabricate components of polymer composites for various biomedical applications. Additionally, we highlight the potential of metal oxides for various drug delivery in terms of their bioactivity and biocompatibility. © 2023 selection and editorial matter, Ram K. Gupta; individual chapters, the contributors.